My street food kitchen fast and easy flavours from around the world - Joyce, Jennifer
"The recipes in My street food kitchen represent a diverse and tantalising range of food discoveries, organised into regional chapters covering new American food; Mexico & South America ; the flavours of the Mediterranean ; the Middle East ; the best of China 7 Taiwan ; Japan & Korea ; South-East Asia ; and India"